Inna Pavlovna Gavrilyuk (1939–2022): (in memory of the scientist) - A. V. Konarev (Труды по прикладной ботанике, генетике и селекции)
On behalf of the VIR team, Department of Biochemistry and Molecular Biology. Compiled by: A.V. Konarev